2019
DOI: 10.1523/jneurosci.2739-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate Cortex to Ventral Hippocampus Circuit Mediates Contextual Fear Generalization

Abstract: Contextual fear memory becomes less context-specific over time, a phenomenon referred to as contextual fear generalization. Overgeneralization of contextual fear memory is a core symptom of post-traumatic stress disorder (PTSD), but circuit mechanisms underlying the generalization remain unclear. We show here that neural projections from the anterior cingulate cortex (ACC) to ventral hippocampus (vHPC) mediate contextual fear generalization in male mice. Retrieval of contextual fear in a novel context at a rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 46 publications
3
62
0
Order By: Relevance
“…Our data showed functional connectivity changes occurred in the hippocampus 24 hr after the onset of cohabitation (ACC–vHIP, LS–dHIP; Figure 5 ), which has demonstrated to be critical in encoding spatial and mnemonic information in rodents ( Lin et al, 2017 ). ACC–vHIP activity has been associated with the regulation of fear in novel environments and in contextual fear generalization in rodents ( Bian et al, 2019 ). However, the vHIP has also shown to contribute in social memory processing ( Chiang et al, 2018 ), and the ACC is proposed to integrate new information to modify future behavior ( Kolling et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed functional connectivity changes occurred in the hippocampus 24 hr after the onset of cohabitation (ACC–vHIP, LS–dHIP; Figure 5 ), which has demonstrated to be critical in encoding spatial and mnemonic information in rodents ( Lin et al, 2017 ). ACC–vHIP activity has been associated with the regulation of fear in novel environments and in contextual fear generalization in rodents ( Bian et al, 2019 ). However, the vHIP has also shown to contribute in social memory processing ( Chiang et al, 2018 ), and the ACC is proposed to integrate new information to modify future behavior ( Kolling et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter (ACC→NAc) connection is functionally reduced in first-episode schizophrenia ( Lin et al, 2018 ). The ACC also projects to further key structures of the extended vSub/VTA circuit, such as the amygdala and the vHC ( Figure 2 )—these connections are crucial for attribution of the appropriate levels of significance during associative learning ( Bian et al, 2019 ; Ortiz et al, 2019 ).…”
Section: Limitations and Challenges Of Harnessing The Hippocampus→nacmentioning
confidence: 99%
“…The dHIP-DG increase in connectivity may be related to partner-memory consolidation, since it has been shown that the DG plays an important role in social recognition (Kesner, 2018). Also, ACC-vHIP activity has been previously associated with the regulation of fear in novel environments and in contextual fear generalization in rodents (Bian et al, 2019). However, the ventral regions of CA1 and CA3 have also shown to contribute in social memory processing (Chiang et al, 2018; S. B.…”
Section: Discussionmentioning
confidence: 99%